Multi Feature Based Classifier for Spectrum Sensing in Cognitive Radio - C.S Kaushik, V; Kolangiammal, S; E Manoj Kumar, B (International Journal of Engineering and Technology, 2018)
Cognitive Radio (CR) is an important technology which can enable the implementation of Dynamic Spectrum Access, which is a paradigm shift from the static spectrum access model. It is an intelligent wireless communication system which can sense the environment and can take decisions to effectively use the available radio resource without creating any interference to the Licensed Primary Users.   Hence sensing of the spectrum plays a very important role in the effective implementation of this technology. We propose a new spectrum sensing algorithm in this paper which is based on machine learning and uses a Multi Feature based Classifier (MFC) model for classification of the spectrum.
Keywords: Dynamic Spectrum Access; Cognitive Radio; Machine Learning; Spectrum Sensing; Multi Feature Based Classifier